General Legal and Opinion Writing Skills: Issues and Explanations - Arowosaiye, Yusuf Ibrahim (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
A discourse on legal and opinion writing is a complex exercise.  This is so because it is difficult to recommend a particular style of legal writing and almost impossible to attain a flawless piece of writing.  Regardless of the challenge, the art of clear communication, speaking and writing form the fulcrum of the fundamental activities of a legal practitioner, paralegal, corporate or academic lawyer.  The importance of good communication skills in the practice of law cannot be over emphasized and this has influenced the inclusion in the curriculum of many law schools modules on opinion writing, drafting of legal documents and advocacy.  Beyond the inclusion in the curriculum of law schools, legal professional bodies and bar associations also recognised the importance of the acquisition of legal writing skills by practitioners.  This paper presents a general overview of qualities of good legal and opinion writing.  This is achieved through the exploration of the basic aspects of written word skills.  The primary objective of this paper therefore is to raise awareness among law students, barristers, and paralegals, the importance of developing skills in legal and opinion writing skills to improve their efficiency and effectiveness in the administration of justice.